2013
DOI: 10.1016/j.bpj.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

An Excess-Calcium-Binding-Site Model Predicts Neurotransmitter Release at the Neuromuscular Junction

Abstract: Despite decades of intense experimental studies, we still lack a detailed understanding of synaptic function. Fortunately, using computational approaches, we can obtain important new insights into the inner workings of these important neural systems. Here, we report the development of a spatially realistic computational model of an entire frog active zone in which we constrained model parameters with experimental data, and then used Monte Carlo simulation methods to predict the Ca(2+)-binding stoichiometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 56 publications
1
58
0
Order By: Relevance
“…Once close to the CaV (< ∼45 nm), additional tethering occurs, as supported by the visualization of multiple short tethers (Fernández-Busnadiego et al, 2013; Wong et al, 2014; Cole et al, 2016). A requirement for a second, L-tethering mechanism was dictated by the need to bring the docked SV within range of the single channel Ca 2+ domain (Fogelson and Zucker, 1985; Simon and Llinás, 1985; Weber et al, 2010), estimated from functional and structural studies to be ∼25 nm (Stanley, 1993, 1997, 2016; Weber et al, 2010; Dittrich et al, 2013). Based on earlier work that reported that the exocytosis-related protein Syntaxin 1A can bind to a characterized ‘synprint’ sequence on the channel II–III loop (Sheng et al, 1998; Catterall, 1999; Atlas, 2001) and the effect of block of this interaction (Mochida et al, 1996), we speculated that this link might account for L-tethering.…”
Section: Discussionmentioning
confidence: 99%
“…Once close to the CaV (< ∼45 nm), additional tethering occurs, as supported by the visualization of multiple short tethers (Fernández-Busnadiego et al, 2013; Wong et al, 2014; Cole et al, 2016). A requirement for a second, L-tethering mechanism was dictated by the need to bring the docked SV within range of the single channel Ca 2+ domain (Fogelson and Zucker, 1985; Simon and Llinás, 1985; Weber et al, 2010), estimated from functional and structural studies to be ∼25 nm (Stanley, 1993, 1997, 2016; Weber et al, 2010; Dittrich et al, 2013). Based on earlier work that reported that the exocytosis-related protein Syntaxin 1A can bind to a characterized ‘synprint’ sequence on the channel II–III loop (Sheng et al, 1998; Catterall, 1999; Atlas, 2001) and the effect of block of this interaction (Mochida et al, 1996), we speculated that this link might account for L-tethering.…”
Section: Discussionmentioning
confidence: 99%
“…The number of VGCCs associated with each vesicle was further investigated by Dittrich et al () using a computational model of a frog NMJ AZ. This model allows for the tracking of individual calcium ions emanating from specific VGCCs as they diffuse throughout the model space.…”
Section: How Many Vggcs Contribute To Vesicle Fusion At the Frog Nmj?mentioning
confidence: 99%
“…This model allows for the tracking of individual calcium ions emanating from specific VGCCs as they diffuse throughout the model space. Constraining free parameters with known anatomical and physiological values, they discovered that functional measures such as the magnitude and timing of neurotransmitter release could be recapitulated if each synaptic vesicle was paired with a single, closely associated VGCC (Dittrich et al, ; Shahrezaei, Cao, & Delaney et al, ). Consistent with these data, Luo, Dittrich, Cho, Stiles, and Meriney et al () demonstrated that when a vesicle was triggered to fuse, it was nearly always accompanied by the opening of its most closely associated channel (94%).…”
Section: How Many Vggcs Contribute To Vesicle Fusion At the Frog Nmj?mentioning
confidence: 99%
“…To aid in the interpretation of these data, and to advance new hypotheses that could be tested experimentally, Dittrich and colleagues (Ma et al 2010, 2011; Dittrich et al 2013) developed a detailed computer model of a frog NMJ active zone and investigated it using spatially realistic Monte‐Carlo diffusion–reaction simulations via the computer program MCell (Monte Carlo Cell; Kerr et al 2008). Their model included a realistic active zone geometry (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, enables the study of nanodomain versus microdomain coupling of Ca 2+ channels to vesicle release. Simulation results for the frog NMJ active zone have already shown the highly localized nature of the interaction of Ca 2+ ions from voltage‐gated Ca 2+ channels with nearby binding sites on vesicles (nanodomain coupling; Ma et al 2011; Dittrich et al 2013).…”
Section: Introductionmentioning
confidence: 99%